(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In the present paper, several coincidence fixed point theorems established for mappings satisfying contractive conditions related to a non-Decreasing Ï†-maps in partially ordered complete generalized Dâˆ—-metric spaces where the cone is not necessarily normal which is the main result of our article.